Pregnancy Outcomes among Adolescent Tribal Women: Insights from South-East Rajasthan, India - Hemant Patidar (Epidemiology, Biostatistics and Public Health)
Abstract Background: Adolescent pregnancy has been common in India and it hosts to several health consequences to the mothers and children. A detailed investigation of the prevalence and consequences of adolescent pregnancy is required. Objective: This study, thus, examines the association of pregnancy outcomes among adolescent women with various socio-cultural, economic and demographic backgrounds. Material & Methods: This study is based on primary data collected from ever married tribal women of south-eastern districts of Rajasthan, India. The birth outcomes of first order pregnancy have been considered to highlight the adolescent pregnancy. Analyses have been done by employing SPSS 16.0. Results: 9.7 percent of the total pregnancies conceived ever by the all respondents and 15.4 percent of total first order pregnancies have been reported to have terminated into non-live births. Women who experienced their first pregnancy at age 20 and above are 3.889 times (p<0.01) more likely tohave live birth outcome than to women of 16 years. Meena women are 1.95 times (p<0.05) more likely to experience live pregnancy outcome than counterpart Bhil women. Women belonging to rich wealth index are significantly 4 times (p<0.01) more likely to give live births. Conclusion: results demonstrate that considerable share of pregnancies among adolescent women turn into miscarriages and this prevalence is more likely among young, rural, uneducated and poor women than their counterpart women. Hence, it is an urgent need to enhance the awareness and improve the socio-economic conditions of tribal women for better health outcomes of mothers and children.   Keywords: Adolescent pregnancy, pregnancy outcomes, tribal women, maternal age, socio-economic factors